Technological Approaches in the Analysis of Extracellular Vesicle Nucleotide Sequences - Tesovnik, Tine; Jenko Bizjan, Barbara; Šket, Robert; Debeljak, Maruša; Battelino, Tadej; Kovač, Jernej (Frontiers in Bioengineering and Biotechnology, 2021)
Together with metabolites, proteins, and lipid components, the EVs cargo consists of DNA and RNA nucleic acid species, which are part of the intracellular communication network regulating specific cellular processes and provoking distinct target cell responses. The nucleic acid extracellular vesicles (EVs) cargo molecules are often investigated in association with a particular pathology and may provide an insight into the physiological and pathological processes in hard-to-access organs and tissues. The diversity and biological function of EVs nucleic sequences is distinct regarding EVs subgroups and differs in tissue and cell released EVs. EVs DNA is present mainly in apoptotic bodies, while there are different species of EVs RNA in all subgroups of EVs. A limited sample volume of unique human liquid biopsy provides a small amount of EVs with limited isolated DNA and RNA, which can be a challenging factor for EVs nucleic acid sequences analysis, while the additional difficulty is technical variability of molecular nucleic acid detection. Advanced next-generation sequencing techniques allow the detection of total EVs genomic or transcriptomic data even at the single-molecule resolution and thus offering a sensitive and accurate EVs DNA or RNA biomarker detection. Additionally, with the process where the EVs genomic or transcriptomic data profiles are compared to identify characteristic EVs differences in specific conditions, novel biomarkers could be discovered. Therefore, a suitable differential expression analysis is crucial to define the EVs DNA or RNA differences between conditions under investigation. Further bioinformatics analysis can predict molecular cell targets and identify targeted and affected cellular pathways. The prediction target tools with functional studies are essential to help specify the role of the investigated EVs nucleic acid targeted sequences in health and disease and support further studies with the intention to promote the development of EVs-related therapeutics. This review will discuss the biological diversity of human liquid biopsy-obtained EVs nucleic sequence DNA and RNA species reported as potential biomarkers in health and disease and methodological principles of their detection, from human liquid biopsy EVs isolation, EVs nucleic acids sequences extraction, techniques for their detection, and their cell target prediction.